CD3ε+ Cells in Pigs With Severe Combined Immunodeficiency Due to Defects in ARTEMIS - Boettcher, Adeline N.; Cino-Ozuna, A. Giselle; Solanki, Yash; Wiarda, Jayne E.; Putz, Ellie; Owens, Jeana L.; Crane, Sara A.; Ahrens, Amanda P.; Loving, Crystal L.; Cunnick, Joan. E.; Rowland, Raymond R. R.; Charley, Sara E.; et al. (Frontiers in Immunology, 2020)
Severe combined immunodeficiency (SCID) is described as the lack of functional T and B cells. In some cases, mutant genes encoding proteins involved in the process of VDJ recombination retain partial activity and are classified as hypomorphs. Hypomorphic activity in the products from these genes can function in the development of T and B cells and is referred to as a leaky phenotype in patients and animals diagnosed with SCID. We previously described two natural, single nucleotide variants in ARTEMIS (DCLR1EC) in a line of Yorkshire pigs that resulted in SCID. One allele contains a splice site mutation within intron 8 of the ARTEMIS gene (ART16), while the other mutation is within exon 10 that results in a premature stop codon (ART12). While initially characterized as SCID and lacking normal levels of circulating lymphoid cells, low levels of CD3ε+ cells can be detected in most SCID animals. Upon further exploration, characterization within ART16/16, ART12/16, and ART12/12 SCID pigs had abnormally small populations of CD3ε+ cells, but not CD79α+ cells, in circulation and lymph nodes. Newborn pigs (0 days of age) had CD3ε+ cells within lymph nodes prior to any environmental exposure. CD3ε+ cells in SCID pigs appeared to have a skewed CD4α+CD8α+CD8β- T helper memory phenotype. Additionally, in some pigs, rearranged VDJ joints were detected in lymph node cells as probed by PCR amplification of TCRδ V5 and J1 genomic loci, as well as TCRβ V20 and J1.1, providing molecular evidence of residual Artemis activity. We additionally confirmed that TCRα and TCRδ constant region transcripts were expressed in the thymic and lymph node tissues of SCID pigs; although the expression pattern was abnormal compared to carrier animals. The leaky phenotype is important to characterize, as SCID pigs are an important tool for biomedical research and this additional phenotype may need to be considered. The pig model also provides a relevant model for hypomorphic human SCID patients.